Mad Max -- Spare-Parts Heroes, Recycled Narratives, Reused Visualities and Recuperated Histories. - POP, DORU (Caietele Echinox, 2015)
The main assumption of this paper is that the mechanisms science fiction cinema uses follow three directions in order to create new representations. One is the cinema narratives that develop new worlds by simply mimicking the present day political and cultural contexts. In their critical form, these are negations of present. Another major function is that of future projections using past histories and mythologies. In their negative form, they are often dystopian worlds. This dichotomy between the utopian vs. dystopian representations has been raised and dealt with in art and literature. Yet the divide between utopian (as modern, positive future projection) and dystopian (as postmodernism, defective representation) is described by the author as limited. The method used to move beyond is the negation of negation, practiced as an interpretative principle, which can deal with the issue of retroactive projections. In order to provide some answers to these complex problems, the author uses examples from the cult series "Mad Max", analyzed as a coherent case study.